Activities in the Nordic graduate school of mathematics education during 2005 - Grevholm, Barbro (NOMAD Nordic Studies in Mathematics Education, 2005)
At it’s meeting in January 2005, the board of the Nordic Graduate School planned for a selection of activities during 2005 for both doctoral students and supervisors. We will give some information about these activities here.